Preliminary Evaluation of Some Engineering Geological Properties of Soils in the New Yenagoa Town, Bayelsa State, Central Niger Delta - PO Youdeowei; HO Nwankwoala (Journal of Applied Sciences and Environmental Management)
The subsurface investigation was undertaken by drilling of ten near the shore drill holes using rotary type drill machine. The boreholes were spaced 100m apart along the 1.2 km long river channel and drilled down to a maximum of 10m. The litho-log reveals light to dark brown, fine grained, cohesionless, loose, sands generally overlying dark grey, very fine grained, soft consistency, sticky, low plasticity, silty clays. Between the two major soil types is an intercalation of a 2.5m thick stratum of dark grey, fine grained, sticky, non-plastic silty sand in Borehole 1 (BH 1). BH 2 to BH 10 present single to two layered stratigraphy of the commonly occurring fine sand and silty clay in various thicknesses to the maximum drilled depth of 10m. Grain size analysis results show a range of poorly graded (well sorted) sands with uniform gradation curves and very little or no fines (0.08 to 6.56% passing of 0.075mm sieve). Specific gravity values ranged from 2.38 to 2.60 and generally low as a result of the fine grained nature of the sandy soils. Results also show a low plasticity range of 4.25 to 13.17% for the silty clay soils, with the sandy soils being non-plastic. Generally, apart from BH 2, BH 3, and BH 4, there is a nonuniform correlation of the boreholes, with the sands occurring as single layers in BH 5, BH 9 and BH 10. The homogeneous uniformity is an indication of deposition under similar energy conditions. Therefore, adequate attention should be given to the likely physical environmental degradation of river bank failure and liquefaction condition that may evolve as a result of dredging/reclamation work in the area.